Global politics - Heywood, Andrew (Palgrave foundations series, 2011)
"This book is a major new introduction to international relations/global politics. Written by a leading textbook author, it is engaging, stimulating and forward-looking, covering all the topics and theory students require at an introductory level"--Provided by publisher.